The effects of exchange rate volatility on tourist flows: evidence from the UK and Sweden. (2015) - Agiomirgianakis, George; Serenis, Dimitris; Tsounis, Nicholas
Exchange rate volatility (ERV) affects international tourist flows either by affecting the choices of the potential traveller or the actions of the tourism intermediaries. In this study, we examine the relationship between tourist arrivals and ERV for the UK and Sweden. Our results show that there is a negative relationship between ERV and tourist flows into the two countries suggesting that potential travellers and tour operators react to changes of the exchange rate. Direct policy implications are: policy makers should consider the effects of ERV when designing tourism policy, i.e. countries with substantial tourist inflows from a diversified range of international markets should avoid the opening up of markets that may be exposed to disturbances that could result to ERV. Further, a country relying heavily on its tourism industry, should avoid using exchange rate policies in order to correct its international competiveness, as these policies may end up to an ERV that could reduce substantially its tourism inflows.